Application of Audio Visual Media to Increase Students' Interest in Learning the Material of the Stories of the Prophets and Apostles in Grade IV of SD 027 Rambah in the Odd Semester of the 2024/2025 Academic Year - Nurlaili, Nurlaili (Indonesian Journal of Basic Education, 2024)
This study aims to improve students' understanding of prayer material through the use of picture media in class IV SD 027 Rambah in the odd semester of the 2024/2025 academic year. The problem in this study is the low understanding of students in recognising the movements and recitation of prayers. The research method used was Classroom Action Research (PTK) carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 24 fourth grade students. The instruments used include observation sheets, comprehension tests, and documentation. The results showed an increase in students' understanding of the prayer material from cycle I to cycle II. In cycle I, students' learning completeness only reached 62.5%, while in cycle II it increased to 87.5%. This shows that the use of picture media can help students understand the material more concretely and interestingly.